2021
DOI: 10.3390/rs13040684
|View full text |Cite
|
Sign up to set email alerts
|

Spatial–Temporal Vegetation Dynamics and Their Relationships with Climatic, Anthropogenic, and Hydrological Factors in the Amur River Basin

Abstract: Information about the growth, productivity, and distribution of vegetation, which are highly relied on and sensitive to natural and anthropogenic factors, is essential for agricultural production management and eco-environmental sustainability in the Amur River Basin (ARB). In this paper, the spatial–temporal trends of vegetation dynamics were analyzed at the pixel scale in the ARB for the period of 1982–2013 using remotely sensed data of long-term leaf area index (LAI), fractional vegetation cover (FVC), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 92 publications
1
4
0
Order By: Relevance
“…The statistical indicators of the calibration and validation phases show the satisfactory performance of the model throughout the basin, mainly upstream and downstream. The obtained results follow other studies, which emphasize the good performance of the SWAT model in modeling Cerrado basins (e.g., [21,27,28,30,31,71]); therefore, the impacts of LULCC on the streamflow time series can be assessed using the calibrated and validated SWAT model. 12 compares annual differences in sediment yield for scenarios S1, OS, and PS.…”
Section: Hypothetical Land Use Scenarios and Simulation Of Runoff-ero...supporting
confidence: 85%
See 1 more Smart Citation
“…The statistical indicators of the calibration and validation phases show the satisfactory performance of the model throughout the basin, mainly upstream and downstream. The obtained results follow other studies, which emphasize the good performance of the SWAT model in modeling Cerrado basins (e.g., [21,27,28,30,31,71]); therefore, the impacts of LULCC on the streamflow time series can be assessed using the calibrated and validated SWAT model. 12 compares annual differences in sediment yield for scenarios S1, OS, and PS.…”
Section: Hypothetical Land Use Scenarios and Simulation Of Runoff-ero...supporting
confidence: 85%
“…The problem of the impacts of agricultural expansion and its implications on runofferosion processes in the Cerrado biome has been widely studied [23][24][25][26]; however, studies involving the flow behavior and the sediment yield in hypothetical LULC scenarios at a basin-scale in this Brazilian biome are still scarce [27][28][29]. For these reasons, the impacts of LULCC on streamflow and sediment yield still need to be further investigated in the Cerrado biome, which is of extreme importance for water resources and electrical production in Brazil [30].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, related studies showed that the calculated potential evapotranspiration of crop was also decreasing for the SJP (Ren et al, 2019). On the other hand, the prolongation of plant growth period and the increase of biomass caused by climate warming would also increase water consumption (Zhou et al, 2021). However, the plant growth period set in ESSI-3 model for this study was constant.…”
Section: The Spatial-temporal Variations Of the Gw Flow And Storage I...mentioning
confidence: 98%
“…Variations in land cover are closely related to the human living environment (Gao et al, 2022; Zhang, Jiang, et al, 2022). Vegetation dynamics are mainly influenced by both climate change and human activities (Ge et al, 2021; Li et al, 2022; Zhou et al, 2021). In terms of greening trends, 35% is attributed to climate change, while 65% is associated with human factors (Qiao et al, 2021).…”
Section: Introductionmentioning
confidence: 99%